Relationships between Communication Satisfaction and Organizational Commitment of Academic Staff in a Selected Public University - Ahmad, Azhar (2004)
This study was undertaken to examine the relationships between communication satisfaction and organizational commitment of academic staff in a selected public university. The study was also aimed at identifying the role of selected demographic factors on organizational commitment. Stratified random sampling was employed in the sample selection and a total of 252 academic staff participated in the survey by returning the self-administered questionnaire distributed to them. Statistical analysis used in the study included descriptive statistics, t-test, ANOVA, Pearson Correlation, and Multiple Regression using both enter and stepwise methods. Based on the study, it has been found that more academic staff were moderately satisfied with the communication practices in the university. Among the eight dimensions of communication satisfaction, subordinate communication achieved the highest satisfaction level as rated by the respondents. In terms of organizational commitment, the academic staff had high affective commitment and moderate continuance and normative commitments. Gender, tenure, and position were observed to differ significantly only in terms of respondents7 affective commitment. Higher affective commitment was observed mostly from the professors and associate professors and from those who had been with the university for more than 20 years. Results of correlation analysis showed significant bivariate relationships between the eight dimensions of communication satisfaction and organizational commitment. However, multiple regression analysis revealed that only four dimensions of communication satisfaction were significant predictors of organizational commitment. Media quality, horizontal communication, and organizational integration were observed to be good predictors of affective commitment. While media quality and horizontal communication were found to be predictors of continuznce commitment, communication climate tended to be a significant predictor of normative commitment. The study has shown that communication satisfaction plays an important and direct role in the organizational commitment of the respondents. The results suggest that in order to increase the organizational commitment of the academic staff, the selected university should improve its communication practices especially in the aspects of media quality, horizontal communication, organizational integration, and communication climate. Channels of communication should be developed, improved, and maintained to ensure a better communication atmosphere. Ln addition, the organization should encourage its academic staff to develop their academic career by providing ample opportunities for them to conduct research and further their studies.